A boa-notícia de Jesus Cristo e a cultura urbana atual Perspectivas - Carias, Celso Pinto (Revista Eclesiástica Brasileira, 2003)
O cristianismo, ao longo dos séculos, foi desafiado a manter vivos o entusiasmo e a alegria de anunciar a Boa-Nova de Jesus Cristo. E os desafios sempre aparecem do lado das transformações humanas configuradas num determinado contexto social. Na busca dos sentidos e valores que constituem a existência humana em sociedade, construindo cultura, o valor perene do Evangelho também precisa aprender a dialogar com o processo de transformação sociocultural da realidade humana. Assim, este artigo pretende discutir, sob o ponto de vista do cristianismo católico, a prática pastoral colocada diante da cidade moderna que desafia a Igreja como missionária de Jesus Cristo nos dias de hoje. Abstract: Throughout the centuries, Christianity has been challenged to keep alive the enthusiasm and the happiness surrounding the announcement of the Good Tidings of Jesus Christ. These challenges always appear side by side with the human changes that occur in a given social context. In the search for meanings and values that make up human existence in society and lead to the construction of culture, the perennial principles of the Gospel must also learn how to maintain a dialogue with the process of the social cultural transformation of human reality. Thus the objective of this article is to discuss, under the perspective of Catholic Christianity, the pastoral practice in the face of the modern city – a city that today questions the Church’s role as Jesus Christ’s missionary.